2003
DOI: 10.1159/000070120
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin G20210A Mutation, but Not Factor V Leiden, Is a Risk Factor in Patients with Persistent Foramen ovale and Otherwise Unexplained Cerebral Ischemia

Abstract: Background: Paradoxical embolism via persistent foramen ovale (PFO) is suspected to be a frequent cause of stroke in younger patients. We investigated whether the prevalence of the risk factors for venous thrombosis factor V Leiden (FVL) and prothrombin G20210A mutation (PT G20210A) is increased in this group of patients. Methods: We examined FVL and PT G20210A mutation in 220 patients (group 1) with cerebral ischemia associated with a PFO and without other etiology, in 196 patients with cerebral ischemia of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 17 publications
2
30
1
Order By: Relevance
“…The present data are consistent with previous reports [11][12][13] and have important clinical implications. From a clinical viewpoint, it is critical to define in which cases PFO per se constitutes a risk high enough to warrant percutaneous closure and then define the best treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present data are consistent with previous reports [11][12][13] and have important clinical implications. From a clinical viewpoint, it is critical to define in which cases PFO per se constitutes a risk high enough to warrant percutaneous closure and then define the best treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the G20210A variant in the PT gene was confirmed to be significantly associated with cerebral ischemia in patients with PFO. [11][12][13] Recently, a case-control study demonstrated that only "major" venous-to-arterial circulation shunts, usually due to PFO, were associated with stroke in young adults, but no relation was found between thrombophilia and ischemic stroke. 20 However, major venous-to-arterial circulation shunts were identified by transcranial Doppler after intravenous microbubble ultrasound contrast in only 24 (25%) patients compared with 12 (12%) control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without limitation to the number of subjects, we identified 9 case-control studies examining the relationship of the inherited thrombophilias, patent foramen ovale (PFO), and stroke 21,24,[37][38][39][40][41][42][43] (Table 3). Sastry et al 9 collected data on both PFO and thrombophilia in ischemic stroke but did not evaluate them in relation to each other.…”
Section: Inherited Thrombophilia and Patent Foramen Ovalementioning
confidence: 99%
“…Sastry et al 9 collected data on both PFO and thrombophilia in ischemic stroke but did not evaluate them in relation to each other. These studies also produced conflicting results, with some studies suggesting an association between PTM or FVL and PFO, 24,[41][42][43] and others finding no relation. 21,[37][38][39][40] None of the studies that examined PC, PS, or AT found any association of these deficiencies with PFO and stroke.…”
Section: Inherited Thrombophilia and Patent Foramen Ovalementioning
confidence: 99%